Sosialisasi Koperasi pada Perempuan Tani Desa Lancang Kuning Kabupaten Bintan - Ismail, Khodijah (Forum Kerjasama Pendidikan Tinggi, 2022)
Cooperatives base their activities on the principle of people's economic movement based on the principle of kinship, their presence in rural and coastal areas is expected to be able to prosper groups of people who are far from urban areas. However, the existence of cooperatives until now has not attracted the attention of most people, especially women. Factors causing the absence of fisher farming women joining cooperatives in this village before this activity was carried out were; 1) this village has never received cooperative socialization, 2) the community's dependence on village-wide credit loans, 3) the negative perception of some people towards cooperative institutions, 4) the consumptive lifestyle of the village community. This community service activity aims to socialize village communities about the important role of cooperatives and motivate women-fisherman groups in villages to develop their businesses through cooperatives. The results of community service activities that have been carried out in Lancangkuning Village, Bintan Regency show that the community of women farmers and fishermen are beginning to understand opportunities to improve the economy through cooperatives. After following the socialization, their knowledge of cooperatives increases and they have a strong desire to get rid of loans from moneylenders.